Wood high-temperature plasticizing compression enhancing method and solid wood material thereof
Through the high-temperature plasticization compression enhancement method, the mass loss and odor problems caused by unstable wood mechanical strength and high-temperature humidity and heat treatment are solved, and the improvement of wood mechanical strength and stability are achieved.
Patent Information
- Application Number
- CN202510059663.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-10-22
- Filing Date
- 2025-01-15
- Publication Date
- 2025-03-14
AI Technical Summary
The mechanical strength of wood is unstable when the ambient temperature and humidity change, and the existing high-temperature and humidity treatment methods lead to wood mass loss and odor generation.
The high-temperature plasticization compression enhancement method is adopted to achieve plastic compression of wood and solidification of cellulose through the preheating step and controlling the pressure and feed speed in the compression step, thereby reducing the hydrophilicity and odor generation of wood.
It improves the mechanical strength of the wood, reduces the sensitivity to ambient temperature and humidity, maintains the original color and odor of the wood, and does not produce odor or mass loss during the treatment process.
Smart Images

Figure CN119610311A_ABST
Abstract
Description
[0001] This application claims priority to a patent application with application number 202411474553.0, filing date October 22, 2024, and titled “A method for high-temperature plasticization and compression strengthening of wood and its actual wood material”. Technical Field
[0002] The present invention relates to the technical field of wood modification, and in particular to a method for high temperature, plasticization and strengthening of wood; the present invention also relates to a product of the wood high temperature plasticization and strengthening method, which is a solid wood material that retains the natural properties of the log and has high mechanical strength and stability. Background Art
[0003] Wood has good machinability, mechanical strength, thermal conductivity and insulation (in dry state), and is an important building and decoration material. At the same time, wood also has natural color and texture and can be used for decoration. However, below the fiber saturation point, many physical properties of wood are affected by moisture content, especially the mechanical strength of wood. Changes in ambient temperature and humidity will affect the moisture content of wood, and then change the mechanical strength of wood. In other words, when the ambient humidity changes greatly, the strength of wood is unstable. This change is specifically manifested in that as the moisture content of wood increases, the mechanical strength of wood decreases linearly.
[0004] When the wood reaches a moisture content equilibrium state in the environment of 20℃ / 45%RH and 30℃ / 92%RH respectively, the mechanical strength of the wood in the latter condition decreases by about 40-50% compared with the former. When the moisture content of the wood is higher than the fiber saturation point in the high temperature and humid environment, the wood is prone to decay, which weakens the mechanical strength of the wood to a greater extent.
[0005] Obviously, the material property that the mechanical strength of wood is affected by its own moisture content limits the application of wood in more occasions.
[0006] The prior art proposes to implement a combined compression-high temperature and wet heat modification treatment on wood to retain the mechanical strength of the wood to a certain extent and weaken the hydrophilicity of the wood. However, according to practice, when the treatment temperature of the high temperature and wet heat treatment is low, the compression fixation is insufficient and the compressed wood still has hydrophilicity. For example, after the compressed wood is subjected to a high temperature and wet heat treatment of 160~180℃, the compression rebound is more than 50%, the equilibrium moisture content of the compressed wood in a 30℃ / 92%RH environment is about 12~16%, and the mechanical strength of the compressed wood decreases with the increase of its moisture content. On the contrary, when the treatment temperature of the high temperature and wet heat treatment is high, although the compression fixation can be basically achieved and the hydrophilicity of the wood can be weakened to a large extent, the quality loss and mechanical strength loss of the wood are serious. For example, after the compressed wood was subjected to a high temperature and wet heat treatment at 240~260℃, the compression rebound dropped to about 20%, and the equilibrium moisture content of the compressed wood in a 30℃ / 92%RH environment dropped to 10~12%, but the mass loss of the wood reached more than 30%, and the mechanical strength of each item was reduced by more than 30%, and the mechanical strength of the compressed wood still had a linear relationship with the change in moisture content. At the same time, the process of compression-high temperature and wet heat combined modification treatment will produce a strong odor, and the compressed wood obtained has a strong odor. Compared with the original appearance of the wood, the wood color has changed significantly, specifically, the wood color is dark brown. Summary of the invention
[0007] The present application provides a method for high-temperature plasticization and strengthening of wood, which can improve the mechanical strength of wood, with only extremely low mass loss in the treatment process, and no odor is generated during the treatment process or in the solid wood material obtained by the treatment; the solid wood material obtained by the method has extremely weak hydrophilicity, and the degree to which the mechanical strength is affected by the ambient temperature and humidity is significantly reduced, and the original color and appearance of the wood can be retained to a certain extent.
[0008] One aspect of an embodiment of the present application provides a method for high-temperature plasticization and compression strengthening of wood, which comprises the following steps in sequence: Preparation step: placing sawn timber with a moisture content of 0±3% on the surface of the lower pressing plate, and the temperature of the upper pressing plate and the lower pressing plate is 220-240° C.; A preheating step, wherein the upper pressing plate contacts the upper surface of the sawn timber for 30 to 90 seconds; In the compression step, the upper pressing plate is pressed down at a pressure of 3.5-4.5 MPa, and the pressing feed speed is 4.5-5.0 mm / min; In the pressure-maintaining step, the upper pressing plate and the lower pressing plate are both cold plates, and the pressure is maintained for 200 to 300 seconds; The pressure relief step includes pressure relief and discharging to obtain solid wood material.
[0009] By means of the above method, the mechanical strength of sawn timber can be improved, and only very low mass loss occurs during the treatment process, and no odor is generated; the solid wood material obtained by the treatment has no odor, low hydrophilicity, and the mechanical strength is almost unaffected by the ambient temperature and humidity, the color of the wood does not change, and even after boiling in water, the mechanical strength is only slightly reduced.
[0010] Specifically, under the premise that the sawn wood is in a low moisture content state and the hot compression temperature is higher than the softening temperature of the wood hemicellulose, the setting of the preheating step and the control of the pressure and feed speed in the compression step are coordinated, so that the wood can be plastically compressed, and the hemicellulose is degraded to the greatest extent during the compression process, but at the same time, the cellulose is not degraded and the lignin is degraded very little. Since the hydroxyl groups of hemicellulose are fully degraded into lignin; the cellulose that has been re-solidified after the compression step and the pressure holding step is not affected by moisture at room temperature, which makes the wood extremely hydrophilic and rigid; at the same time, the undegraded lignin can maintain the original quality and color of the wood, and almost no products such as furfural that cause odor are produced. The solid wood material prepared thereby has good dimensional stability, and the mechanical strength is almost unaffected by the ambient temperature and humidity. This is different from the degradation mechanism of hemicellulose in the compression or high-temperature wet heat treatment of the prior art. In the treatment process of the prior art, hemicellulose is hydrolyzed into acetic acid and water that catalyze the degradation of cellulose, as well as products such as furfural that cause odor.
[0011] The prior art believes that the moisture in the wood can be used as a plasticizer for compression, thereby improving the plasticity of the wood and achieving compression of the wood; or, although there is no moisture in the wood (that is, the wood is in an absolute dry or super absolute dry state), by increasing the compression temperature to above the softening temperature of the wood (240°C), the compression-compression fixation of the wood can be completed in one step. The former must be implemented in conjunction with high-temperature wet heat treatment to fix the compression, and the moisture will undergo complex and uncontrollable migration during the compression process, making it difficult to form a relatively fixed correspondence between the compression process and the compression effect, and the mechanical strength of the obtained wood has a linear relationship with the change in moisture content.
[0012] There is a strong correspondence between the compression process and the effect of the latter, and no additional high-temperature wet heat treatment is required. However, the inventors found that when there is no moisture in the wood, the temperature exceeds 240°C, and the hemicellulose is degraded, which will lead to a large amount of decomposition of lignin, resulting in an increase in the mass loss rate of the wood, a decrease in the mechanical strength of the wood, and a large amount of products such as furfural with peculiar smell, and the color of the wood changes significantly. When the temperature is further increased to more than 280°C, the temperature will cause the cellulose to degrade rapidly, resulting in a significant decrease in the mechanical strength of the wood. This causes the compressed wood to have an odor, and the mechanical strength and quality loss are serious.
[0013] In the technical solution of the present application, the treated wood is in an absolute dry or super absolute dry state, but the hot pressing temperature used does not reach the softening temperature of the wood. At this time, by introducing a preheating step and controlling the pressure and feed speed of the compression step, the problem that the hot compression temperature fails to reach the softening temperature of the wood can be overcome, so that the sawn timber can be compressed smoothly to form a permanent compression strain, and the compression strain can reach 50% without observable cell wall microcracks.
[0014] Preferably, in the preheating step, the contact pressure between the upper pressing plate and the sawn timber is 0.3-0.5 MPa, and the contact pressure lasts for 30-90 seconds.
[0015] Preferably, the compression rate of the solid wood material is not less than 15% compared to the sawn timber.
[0016] Preferably, the compression rate of the solid wood material is 15-50% compared to the sawn timber.
[0017] Preferably, the color change of the solid wood material compared with the sawn wood is ∆E * ≤32%.
[0018] Preferably, during the implementation of the wood high temperature plasticization compression strengthening method, the furfural concentration in the indoor air is detected to be lower than 0.07 mg / m 3 .
[0019] The second aspect of the embodiment of the present application provides a solid wood material obtained by the aforementioned high-temperature plasticization and strengthening method for wood. When the ambient temperature and humidity conditions change from 20°C / 45%RH to 30°C / 92%RH and the moisture content of the solid wood material is balanced and stabilized, the decrease in the surface hardness of the solid wood material does not exceed 15%.
[0020] Preferably, when the ambient temperature and humidity conditions change from 20°C / 45%RH to 30°C / 92%RH, and the moisture content of the solid wood material is balanced and stabilized, the decrease in the bending strength of the solid wood material does not exceed 15%.
[0021] Preferably, after being boiled in water for 2 hours, the surface hardness of the solid wood material decreases by no more than 30%, and the elastic bending strength decreases by no more than 30%.
[0022] Preferably, the cellulose content in the solid wood material is 40-45%, and the lignin content is 32-36%.
[0023] Preferably, the furfural content in the solid wood material is 3-6%.
[0024] Preferably, under the environmental temperature and humidity conditions of 20°C / 45%RH, the equilibrium moisture content of the solid wood material is 3-5%; under the environmental temperature and humidity conditions of 30°C / 92%RH, the equilibrium moisture content of the solid wood material is 7-9%; after being boiled in water for 2 hours, the moisture content of the solid wood material is 60-75%.
[0025] Preferably, the mildew resistance level of the solid wood material is 0~1.
[0026] As is known to all, wood has obvious shrinkage and swelling when wet and inconspicuous thermal expansion and contraction when cold. The solid wood material provided by the present application weakens the shrinkage and swelling of wood and retains the inconspicuous thermal expansion and contraction of wood, thereby obtaining a solid wood material with relatively stable performance. The solid wood material provided by the present application has stable mechanical strength and moisture content. Its mechanical strength, moisture content, wood color and appearance are only affected by the ambient temperature and humidity to a small extent. It has a high mildew resistance level, so it can be suitable for use in a hot and humid environment, and can also adapt to the ambient temperature and humidity, especially the use environment with large humidity changes. At the same time, the solid wood material provided by the present application has no peculiar smell and can be suitable for use in indoor environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative labor.
[0028] Figure 1 (a) is a photo of the sawn timber provided in Example 8 of the present application; Figure 1 (b) is a photo of the solid wood material provided in Example 8 of the present application; Figure 1 (c) a photograph of the control solid wood material provided in Control Example 5 of this application; Figure 1 (d) is a photograph of the control solid wood material provided in Control Example 6 of the present application. DETAILED DESCRIPTION
[0029] In order to enable those skilled in the art to better understand the technical solutions in the present application, the technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of this application.
[0030] A method for high-temperature plasticization and compression strengthening of wood, comprising the following steps in sequence: Preparation step: Place sawn timber with a moisture content of 0±3% on the surface of the lower pressing plate, and the temperature of the upper pressing plate and the lower pressing plate is 220~240℃; The preheating step is to make the upper pressing plate contact the upper surface of the sawn timber with a contact pressure of 0.3-0.5 MPa for a duration of 30-90 seconds; In the compression step, the upper pressing plate is pressed down at a pressure of 3.5-4.5 MPa, and the pressing feed speed is 4.5-5.0 mm / min; In the pressure holding step, both the upper and lower pressing plates are cold plates, and the pressure is maintained for 200-300 seconds; The pressure relief step is to relieve the pressure and discharge the material to obtain the solid wood material.
[0031] In the preparation step, the temperature of the hot plate (upper pressing plate and lower pressing plate) should be less than 240°C. In some cases, the hot plate temperature may be 230°C, which should be adjusted appropriately according to the actual situation. Preferably, the processing temperature is 220-235°C.
[0032] Example 1: A method for high temperature plasticization and compression strengthening of wood, the treatment object is fir sawn timber, the sawn timber thickness is 24.5 mm, the moisture content is 0±0.5%, the target thickness is 20 mm (compression rate is 18.5%), and the specific treatment steps are: (1) Preparation step: Place the sawn timber on the surface of the lower pressing plate. Both the upper pressing plate and the lower pressing plate are hot plates with a temperature of 220-224°C. (2) Preheating step, making the upper pressing plate contact the upper surface of the sawn timber quickly (preferably within 5 seconds), with a contact pressure of 0.3 MPa and a duration of 90 seconds; (3) Compression step: the upper pressing plate is pressed down at a pressure of 3.5 MPa, the pressing feed speed is 4.5 mm / min, and the pressing process takes 60 s; (4) Pressure-maintaining step, using existing technology, such as circulating cold water to cool the upper platen. At this time, both the upper platen and the lower platen are cold plates, but the pressure is maintained for 200 seconds; (5) Pressure relief step: pressure relief and material discharge to obtain solid wood material.
[0033] During the implementation of the above method, the solid wood material retains the original smell of wood, the air in the laboratory has no odor, and no furfural is detected in the air in the laboratory. The solid wood material prepared in this example is marked as serial number 1.
[0034] The detection method for furfural content in laboratory indoor air is carried out in accordance with the formaldehyde concentration determination method in the national standard GB / T 18883-2022 "Indoor Air Quality Standard". This method can detect indoor aldehyde concentrations, but since solid wood materials do not volatilize formaldehyde, the detected aldehyde concentration should be inferred to be furfural concentration.
[0035] Example 2: A method for high temperature plasticization and compression strengthening of wood, the treatment object is fir sawn timber, the sawn timber thickness is 24.5 mm, the moisture content is 0±0.5%, the target thickness is 18 mm (compression rate is 26.5%), and the specific treatment steps are: (1) Preparation step: Place the sawn timber on the surface of the lower pressing plate. Both the upper pressing plate and the lower pressing plate are hot plates with a temperature of 220-224°C. (2) Preheating step, making the upper pressing plate contact the upper surface of the sawn timber quickly (preferably within 5 seconds), with a contact pressure of 0.3 MPa and a duration of 90 seconds; (3) Compression step: the upper pressing plate is pressed down at a pressure of 4 MPa, the pressing feed speed is 4.5 mm / min, and the pressing process takes 87 s; (4) Pressure-maintaining step, using existing technology, such as circulating cold water to cool the upper platen. At this time, both the upper platen and the lower platen are cold plates, but the pressure is maintained for 220 seconds; (5) Pressure relief step: pressure relief and material discharge to obtain solid wood material.
[0036] During the implementation of the above method, the solid wood material retains the original smell of wood, the air in the laboratory has no odor, and furfural is not detected in the air in the laboratory. The solid wood material prepared in this example is marked as serial number 2.
[0037] Example 3: A method for high temperature plasticization and compression strengthening of wood, the processing object is fir sawn timber, the sawn timber thickness is 24.5mm, the moisture content is 0±0.5%, the target thickness is 16mm (compression rate is 35%), and the specific processing steps are: (1) Preparation step: Place the sawn timber on the surface of the lower pressing plate. Both the upper pressing plate and the lower pressing plate are hot plates with a temperature of 220-224°C. (2) Preheating step, in which the upper pressing plate contacts the upper surface of the sawn timber quickly (preferably within 5 seconds), with a contact pressure of 0.4 MPa and a duration of 80 seconds; (3) Compression step: the upper pressing plate is pressed down at a pressure of 4 MPa, the pressing feed speed is 5 mm / min, and the pressing process takes 102 s; (4) a pressure-maintaining step, using existing technology, such as circulating cold water to cool the upper and lower pressing plates, but maintaining the pressure for 260 seconds; (5) Pressure relief step: pressure relief and material discharge to obtain solid wood material.
[0038] During the implementation of the above method, the solid wood material retains the original smell of wood, the air in the laboratory has no odor, and furfural is not detected in the air in the laboratory. The solid wood material prepared in this example is marked as serial number 3.
[0039] Example 4: A method for high temperature plasticization and compression strengthening of wood, the processing object is fir sawn timber, the sawn timber thickness is 24.5mm, the moisture content is 0±0.5%, the target thickness is 14mm (compression rate 43%), the specific processing steps are: (1) Preparation step: Place the sawn timber on the surface of the lower pressing plate. Both the upper pressing plate and the lower pressing plate are hot plates with a temperature of 222~226℃; (2) Preheating step, making the upper pressing plate contact the upper surface of the sawn timber quickly (preferably within 5 seconds), with a contact pressure of 0.5 MPa and a duration of 80 seconds; (3) Compression step: the upper pressing plate is pressed down at a pressure of 4.5 MPa, the pressing feed speed is 5 mm / min, and the pressing process takes 126 s; (4) a pressure-maintaining step, using existing technology, such as circulating cold water to cool the upper and lower pressing plates, but maintaining the pressure for 300 seconds; (5) Pressure relief step: pressure relief and material discharge to obtain solid wood material.
[0040] During the implementation of the above method, the solid wood material retains the original smell of wood, the air in the laboratory has no odor, and furfural is not detected in the air in the laboratory. The solid wood material prepared in this example is marked as serial number 4.
[0041] Example 5: A method for high temperature plasticization compression strengthening of wood, the processing object is poplar sawn timber, the sawn timber thickness is 25mm, the moisture content is 0±1.5%, the target thickness is 20mm (compression rate 20%), the specific processing steps are: (1) Preparation step: Place the sawn timber on the surface of the lower pressing plate. Both the upper pressing plate and the lower pressing plate are hot plates with a temperature of 226-230°C. (2) Preheating step, making the upper pressing plate contact the upper surface of the sawn timber quickly (preferably within 5 seconds), with a contact pressure of 0.3 MPa and a duration of 70 seconds; (3) Compression step: the upper pressing plate is pressed down at a pressure of 3.5 MPa, the pressing feed speed is 4.5 mm / min, and the pressing process takes 67 s; (4) Pressure-maintaining step, using existing technology, such as circulating cold water to cool the upper platen. At this time, both the upper platen and the lower platen are cold plates, but the pressure is maintained for 200 seconds; (5) Pressure relief step: pressure relief and material discharge to obtain solid wood material.
[0042] During the implementation of the above method, the solid wood material retains the original smell of wood, the air in the laboratory has no odor, and furfural is not detected in the air in the laboratory. The solid wood material prepared in this example is marked as serial number 5.
[0043] Example 6: A method for high temperature plasticization compression strengthening of wood, the processing object is poplar sawn timber, the sawn timber thickness is 25mm, the moisture content is 0±1.5%, the target thickness is 18mm (compression rate 28%), the specific processing steps are: (1) Preparation step: Place the sawn timber on the surface of the lower pressing plate. Both the upper pressing plate and the lower pressing plate are hot plates with a temperature of 226-230°C. (2) Preheating step, making the upper pressing plate contact the upper surface of the sawn timber quickly (preferably within 5 seconds), with a contact pressure of 0.3 MPa and a duration of 70 seconds; (3) Compression step: the upper pressing plate is pressed down at a pressure of 3.5 MPa, the pressing feed speed is 4.5 mm / min, and the pressing process takes 94 s; (4) Pressure-maintaining step, using existing technology, such as circulating cold water to cool the upper platen. At this time, both the upper platen and the lower platen are cold plates, but the pressure is maintained for 220 seconds; (5) Pressure relief step: pressure relief and material discharge to obtain solid wood material.
[0044] During the implementation of the above method, the solid wood material retains the original smell of wood, the air in the laboratory has no odor, and furfural is not detected in the air in the laboratory. The solid wood material prepared in this example is marked as serial number 6.
[0045] Example 7: A method for high temperature plasticization compression strengthening of wood, the processing object is poplar sawn timber, the sawn timber thickness is 25mm, the moisture content is 0±1.5%, the target thickness is 16mm (compression rate 36%), the specific processing steps are: (1) Preparation step: Place the sawn timber on the surface of the lower pressing plate. Both the upper pressing plate and the lower pressing plate are hot plates with a temperature of 230-234°C. (2) Preheating step, making the upper pressing plate contact the upper surface of the sawn timber quickly (preferably within 5 seconds), with a contact pressure of 0.3 MPa and a duration of 50 seconds; (3) Compression step: the upper pressing plate is pressed down at a pressure of 3.5 MPa, the pressing feed speed is 5 mm / min, and the pressing process takes 108 s; (4) a pressure-maintaining step, using existing technology, such as circulating cold water to cool the upper and lower pressing plates, but maintaining the pressure for 300 seconds; (5) Pressure relief step: pressure relief and material discharge to obtain solid wood material.
[0046] During the implementation of the above method, the solid wood material retains the original smell of wood, the air in the laboratory has no odor, and furfural is not detected in the air in the laboratory. The solid wood material prepared in this example is marked as serial number 7.
[0047] Example 8: A method for high temperature plasticization compression strengthening of wood, the processing object is poplar sawn timber, the sawn timber thickness is 25mm, the moisture content is 0±1.5%, the target thickness is 14mm (compression rate 44%), the specific processing steps are: (1) Preparation step: Place the sawn timber on the surface of the lower pressing plate. Both the upper pressing plate and the lower pressing plate are hot plates with a temperature of 232-236°C. (2) Preheating step, making the upper pressing plate contact the upper surface of the sawn timber quickly (preferably within 5 seconds), with a contact pressure of 0.4 MPa and a duration of 40 seconds; (3) Compression step: the upper pressing plate is pressed down at a pressure of 4 MPa, the pressing feed speed is 5 mm / min, and the pressing process takes 132 s; (4) a pressure-maintaining step, using existing technology, such as circulating cold water to cool the upper and lower pressing plates, but maintaining the pressure for 300 seconds; (5) Pressure relief step: pressure relief and material discharge to obtain solid wood material.
[0048] During the implementation of the above method, the solid wood material retains the original smell of wood, the air in the laboratory has no odor, and furfural is not detected in the air in the laboratory. The solid wood material prepared in this example is marked as serial number 8.
[0049] Comparative Example 1: The treatment object is fir sawn timber, the sawn timber thickness is 24.5mm, the moisture content is 0±0.5%, the target thickness is 20mm (compression rate is 18.5%), and the specific treatment steps are: (1) Preparation step: Place the sawn timber on the surface of the lower pressing plate. Both the upper pressing plate and the lower pressing plate are hot plates with a temperature of 243-247°C. (2) Compression step, in which the upper pressing plate contacts the upper surface of the sawn timber quickly (preferably within 5 seconds), the upper pressing plate presses down at a pressure of 3.5 MPa, the pressing feed speed is 4.5 mm / min, and the pressing process takes 60 seconds; (3) Pressure relief step: pressure relief and material discharge to obtain a control solid wood material.
[0050] In the implementation of the above method, the solid wood material had a more obvious odor. The air in the laboratory was tested and the furfural concentration was measured to be 0.09 mg / m 3 The control solid wood material prepared in this example is marked with serial number A.
[0051] Comparative Example 2: The treatment object is fir sawn timber, the sawn timber thickness is 24.5mm, the moisture content is 0±0.5%, the target thickness is 14mm (compression rate 43%), and the specific treatment steps are: (1) Preparation step: Place the sawn timber on the surface of the lower pressing plate. Both the upper pressing plate and the lower pressing plate are hot plates with a temperature of 258~262℃; (2) Compression step, in which the upper pressing plate contacts the upper surface of the sawn timber quickly (preferably within 5 seconds) and presses down at a pressure of 4.5 MPa. The pressing feed speed is 5 mm / min and the pressing process takes 126 seconds. (3) Pressure holding step: maintaining temperature and pressure for 300 seconds; (4) Pressure relief step: cooling, pressure relief, and discharging to obtain a control solid wood material.
[0052] In the implementation of the above method, the solid wood material had a more obvious odor, and the air in the laboratory was tested and the furfural concentration was measured to be 0.1 mg / m 3 The control solid wood material prepared in this example is marked with a serial number B.
[0053] Comparative Example 3: The treatment object is fir sawn timber, the sawn timber thickness is 24.5mm, the moisture content is 5-7%, the target thickness is 14mm (compression rate 43%), the specific treatment steps are: (1) Preparation step: Place the sawn timber on the surface of the lower pressing plate. Both the upper pressing plate and the lower pressing plate are hot plates with a temperature of 178~182℃; (2) Preheating step, making the upper pressing plate contact the upper surface of the sawn timber quickly (preferably within 5 seconds), with a contact pressure of 0.4 MPa and a duration of 120 seconds; (3) Compression step: the upper pressing plate is pressed down at a pressure of 4 MPa, the pressing feed speed is 5 mm / min, and the pressing process takes 132 s; (4) Pressure holding step: maintaining temperature and pressure for 300 seconds; (5) Decompression step: cooling, decompression, and discharging to obtain solid wood compressed material.
[0054] Subsequently, the solid wood compression material was subjected to high temperature heat treatment using the existing technology, the treatment temperature was 180°C, the treatment time was 2 hours, and the control solid wood material was obtained after leaving the kiln. During the implementation of the above method, the solid wood material maintained the original smell of the wood, and furfural was not detected in the air in the laboratory. The control solid wood material prepared in this example was marked with serial number C.
[0055] Comparative Example 4: The treatment object is poplar sawn timber, the sawn timber thickness is 25mm, the moisture content is 0±1.5%, the target thickness is 20mm (compression rate 20%), and the specific treatment steps are: (1) Preparation step: Place the sawn timber on the surface of the lower pressing plate. Both the upper pressing plate and the lower pressing plate are hot plates with a temperature of 243-247°C. (2) Compression step: the upper pressing plate is pressed down at a pressure of 3.5 MPa, the pressing feed speed is 4.5 mm / min, and the pressing process takes 67 s; (3) Pressure relief step: pressure relief and material discharge to obtain a control solid wood material.
[0056] During the implementation of the above method, the solid wood material had a more obvious odor. The air in the laboratory was tested and the furfural concentration was measured to be 0.07 mg / m 3 The control solid wood material prepared in this example is marked with a serial number D.
[0057] Comparative Example 5: The treatment object is poplar sawn timber, the sawn timber thickness is 25mm, the moisture content is 0±1.5%, the target thickness is 14mm (compression rate 44%), and the specific treatment steps are: (1) Preparation step: Place the sawn timber on the surface of the lower pressing plate. Both the upper pressing plate and the lower pressing plate are hot plates with a temperature of 258~262℃; (2) Compression step: the upper pressing plate is brought into contact with the upper surface of the sawn timber quickly (preferably within 5 seconds) and pressed down at a pressure of 4 MPa. The pressing feed speed is 5 mm / min and the pressing process takes 132 seconds. (3) Pressure holding step: maintaining temperature and pressure for 300 seconds; (4) Pressure relief step: cooling, pressure relief, and discharging to obtain a control solid wood material.
[0058] During the implementation of the above method, the compressed wood obtained had a distinct odor, and the furfural concentration detected in the laboratory air was 1.5 mg / m 3 The control solid wood material prepared in this example is marked with a serial number E.
[0059] Comparative Example 6: The processing object is poplar sawn timber, the sawn timber thickness is 25mm, the moisture content is 3-5%, the target thickness is 14mm (compression rate 44%), the specific processing steps are: (1) Preparation step: Place the sawn timber on the surface of the lower pressing plate. Both the upper pressing plate and the lower pressing plate are hot plates with a temperature of 178~182℃; (2) Preheating step, making the upper pressing plate contact the upper surface of the sawn timber quickly (preferably within 5 seconds), with a contact pressure of 0.4 MPa and a duration of 120 seconds; (3) Compression step: the upper pressing plate is pressed down at a pressure of 4 MPa, the pressing feed speed is 5 mm / min, and the pressing process takes 132 s; (4) Pressure holding step: maintaining temperature and pressure for 300 seconds; (5) Decompression step: cooling, decompression, and discharging to obtain solid wood compressed material.
[0060] Subsequently, the solid wood compression material was subjected to high temperature heat treatment using the existing technology, the treatment temperature was 180°C, the treatment time was 2 hours, and the control solid wood material was obtained after leaving the kiln. During the implementation of the above method, the treated material retained the original smell of the wood, and furfural was not detected in the air in the laboratory. The control solid wood material prepared in this example was marked with a serial number F.
[0061] Comparative Example 7: Fir sawn timber, thickness 24.5 mm, moisture content 0 ± 0.5%, marked with serial number G.
[0062] Comparative Example 8: Poplar sawn timber, thickness 25 mm, moisture content 0 ± 1.5%, marked with serial number H.
[0063] Tables 1 to 5 show the comparison of appearance quality, chemical composition, equilibrium moisture content and mechanical strength of the solid wood materials prepared in Examples 1 to 8 and Comparative Examples 1 to 6 and the control solid wood materials.
[0064] Table 1
[0065] As can be seen from Table 1, the solid wood material prepared by the technical solution of the present application has no macroscopic and microscopic cracks even when the compression rate reaches more than 40%, which largely ensures the real-time mechanical strength and long-term mechanical strength of the material. By comparing with the test pieces numbered A, B, D, and E, it can be seen that the setting of the preheating step and the control of the pressure and feed speed in the compression step can overcome the problem that the hot compression temperature fails to reach the softening temperature of the wood, so that the sawn wood can be compressed smoothly, and the compression strain can reach 50% without observed macroscopic and microscopic cracks.
[0066] Table 2
[0067] As can be seen from Table 2, under low moisture content or water-free conditions, the specimens numbered A, B, D, and E, because the compression temperature in the compression step exceeds 240°C, the hemicellulose is degraded, the lignin is decomposed in large quantities, and products such as furfural with odor are produced, which make the obtained solid wood material emit odor for a long time. The solid wood material prepared by the technical solution of the present application has relatively less cellulose loss, which ensures the mechanical strength of the material, and forms a certain amount of lignin, which ensures the dimensional stability of the material and makes the material have good hydrophobicity.
[0068] Table 3, equilibrium moisture content / %
[0069] As can be seen from Table 3, by performing a compression step on anhydrous or low-moisture wood at a compression temperature lower than its softening temperature, and coordinating the preheating step, pressure, pressing speed and other parameters to smoothly complete the compression, the lignin in the obtained solid wood material can be increased, thereby making it have a higher hydrophobicity.
[0070] Table 4, Surface hardness
[0071] Table 5. Flexural strength
[0072] It can be seen from Tables 4 and 5 that by performing the compression step on the water-free or low-moisture wood at a compression temperature lower than its softening temperature, and coordinating the preheating step, pressure, pressing speed and other parameters, the compression is successfully completed, which can avoid excessive degradation of cellulose and ensure the cellulose content therein, so that it has a higher mechanical strength. At the same time, through the process of the technical solution of the present application, the mechanical properties of the solid wood material prepared are almost unaffected by the ambient temperature, humidity and moisture content, and are only affected by boiling to a small extent.
[0073] Figure 1 (a) shows a photo of the sawn timber provided in Example 8 of the present application, Figure 1 (b) shows a photo of the solid wood material provided in Example 8 of the present application, Figure 1 (c) shows a photograph of the control solid wood material provided in Control Example 5, Figure 1 (d) shows a photograph of the control solid wood material provided in Control Example 6. Figure 1 It can be seen from the comparison that the technical solution of the present application only changes the color of the sawn timber to a very small extent, and the color of the prepared solid wood material is basically the same as that of the sawn timber.
[0074] The above description is intended to be illustrative and not limiting. Upon reading the above description, many embodiments and many applications beyond the examples provided will be apparent to those skilled in the art. Therefore, the scope of the present teachings should not be determined with reference to the above description, but rather with reference to the appended claims and the full scope of equivalents to which such claims are entitled. For the purpose of comprehensiveness, all articles and references, including disclosures of patent applications and publications, are incorporated herein by reference. The omission of any aspect of the subject matter disclosed herein in the preceding claims is not intended to be a waiver of the subject matter, nor should it be considered that the applicant has not considered the subject matter to be part of the disclosed application subject matter.
Claims
1. A method for high temperature plasticization and compression strengthening of wood, characterized in that: The following steps are included in order: Preparation step: placing sawn timber with a moisture content of 0±3% on the surface of the lower pressing plate, and the temperature of the upper pressing plate and the lower pressing plate is 220-240° C.; A preheating step, wherein the upper pressing plate contacts the upper surface of the sawn timber for 30 to 90 seconds; In the compression step, the upper pressing plate is pressed down at a pressure of 3.5-4.5 MPa, and the pressing feed speed is 4.5-5.0 mm / min; In the pressure-maintaining step, the upper pressing plate and the lower pressing plate are both cold plates, and the pressure is maintained for 200 to 300 seconds; The pressure relief step includes pressure relief and discharging to obtain solid wood material.
2. The wood high temperature plasticization compression strengthening method according to claim 1, characterized in that: In the preheating step, the contact pressure between the upper pressing plate and the sawn timber is 0.3-0.5 MPa.
3. The wood high temperature plasticization compression strengthening method according to claim 1, characterized in that: Compared with the sawn timber, the compression rate of the solid wood material is not less than 15%.
4. A solid wood material, characterized in that: When the ambient temperature and humidity conditions change from 20°C / 45%RH to 30°C / 92%RH, and the moisture content of the solid wood material is balanced and stabilized, the decrease in the surface hardness of the solid wood material does not exceed 15%.
5. The solid wood material according to claim 4, characterized in that: When the ambient temperature and humidity conditions change from 20°C / 45%RH to 30°C / 92%RH, and the moisture content of the solid wood material is balanced and stabilized, the decrease in the bending strength of the solid wood material does not exceed 15%.
6. The solid wood material according to claim 4, characterized in that: After being boiled in water for 2 hours, the decrease in the surface hardness of the solid wood material does not exceed 30%, and the decrease in the bending strength does not exceed 30%.
7. The solid wood material according to claim 4, characterized in that: The cellulose content in the solid wood material is 40-45%, and the lignin content is 32-36%.
8. The solid wood material according to claim 6, characterized in that: The furfural content in the solid wood material is 3-6%.
9. The solid wood material according to claim 4, characterized in that: Under the environmental temperature and humidity conditions of 20℃ / 45%RH, the equilibrium moisture content of the solid wood material is 3~5%; under the environmental temperature and humidity conditions of 30℃ / 92%RH, the equilibrium moisture content of the solid wood material is 7~9%; after boiling in water for 2 hours, the moisture content of the solid wood material is 60~75%.